Risk assessment of musculoskeletal disorders in the field of orthotics prosthetics with RULA and REBA methods - Rahmawati, Rina Fitriana; Supadma, Deby Eka (MEDIA ILMU KESEHATAN, 2024)
Background: PT X,company served custom-made prosthesis orthosis (PO). It has revealed that significant number of PO at PT X operate in non-ergonomic work environments with awkward postures during their work.Objective: This study aims to evaluate PO working posture in connection with their workstations with primary goal of addressing question Methods: Descriptive observational design with cross-sectional approach using total sampling. Research variables are musculoskeletal complaints; were assessed with Nordic Body Questionnare, and work postures; analized with RULA and REBA. Results: Rectification, assembly, grinding, cutting thermoplast sheets, chipping positive cast, and separating plastic from positive cast are workstations which have been identified as significant contributors to musculoskeletal injuries. All activities in those areas are done in standing position. Conclusion: In all activities, PO typically maintain standing posture for extended durations. This has led to development of musculoskeletal injuries required appropriate treatment. It is recommended to improve PO positions during working and enhance their workstations accordingly